Ecological studies on Cyperus difformis, Cyperus iria and Fimbristylis miliacea: three troublesome annual sedge weeds of rice - Chauhan, B.S.; Johnson, D.E. (Wiley, 2009)
Cyperus difformis, Cyperus iria and Fimbristylis miliacea are troublesome annual sedges of rice grown in many countries. Laboratory and screenhouse experiments were conducted to determine the effects of temperature, light, salt and water stress, seed burial depth, and flooding time, duration and depth on germination, emergence and growth of these three species. Germination of all the three species was stimulated by light and warm fluctuating temperatures. Germination of C. difformis was influenced to a greater degree by increasing salt and water stress than C. iria and F. miliacea. In all three species, seeds sown on the soil surface gave the greatest percentage of seedling emergence, and no seedlings emerged from seeds buried in soil at depths of ≥1 cm. Flooding, although not continuous or deep, had a suppressive effect on emergence and growth of C. iria and F. miliacea. Intermittent flooding to shallow depths, however, was less effective in controlling C. difformis; deep flooding was needed to suppress growth of C. difformis seedlings. When the flooding was delayed to 21 days after sowing, there was little growth reduction in all three species.